2016
DOI: 10.1016/j.jaridenv.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed fire effects on resource selection by cattle in mesic sagebrush steppe. Part 2: Mid-summer grazing

Abstract: a b s t r a c tPrescribed fire can release herbaceous forages from woody plant competition thus promoting increased forage plant production, vigor, and accessibility. Prescribe fire also consumes standing litter thereby improving forage quality and palatability. Consequently, prescribed fire is commonly considered an effective tool for manipulating livestock distribution on rangelands. Efficacy of this tool on mesic sagebrush steppe, however, has received little research attention. Beginning in 2001, resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Specifically, the foraging paths in burnt rangelands, despite possibly being longer, become less tortuous, allowing the animals to spend more time foraging and less time traveling between vegetation patches [72]. This was explained by the decrease in competition imposed on herbaceous vegetation by woody plants, with the resultant increase in forage production shortly after the fire [73]. This accords with Pearson et al [74], who reported for the semi-arid grasslands and sagebrush steppe of the Yellowstone National Park, in western USA, that elk (Cervus elaphus) and bison (Bison bison) tended to prefer grazing in post-burnt rangelands, because of greater forage availability than that in non-burnt lands.…”
Section: Post-fire Ungulate Grazingmentioning
confidence: 99%
“…Specifically, the foraging paths in burnt rangelands, despite possibly being longer, become less tortuous, allowing the animals to spend more time foraging and less time traveling between vegetation patches [72]. This was explained by the decrease in competition imposed on herbaceous vegetation by woody plants, with the resultant increase in forage production shortly after the fire [73]. This accords with Pearson et al [74], who reported for the semi-arid grasslands and sagebrush steppe of the Yellowstone National Park, in western USA, that elk (Cervus elaphus) and bison (Bison bison) tended to prefer grazing in post-burnt rangelands, because of greater forage availability than that in non-burnt lands.…”
Section: Post-fire Ungulate Grazingmentioning
confidence: 99%
“…Most rangelands are considered fire-dependent ecosystems, where historical fire regimen maintained under control woodland expansion (Limb et al, 2016). Prescribed fire has been used as a management tool in rangeland ecosystems, for regenerating pastures, because fire can promote forage production, quality and palatability, and also opens up new foraging areas where canopy closure by shrubs obstructed the access to grasslands areas (Hobbs and Spowart, 1984;Cook et al, 1994;Cubit, 1996;Collins et al, 1998;Fernandes et al, 2013;Clark et al, 2016;Santín and Doerr, 2016). Although there is large knowledge on the effects of fire on forests (Pausas et al, 2008;Fernandes et al, 2013;Santín and Doerr, 2016), the response of ecosystems to fire is still not fully understood because it depends on the spatial and temporal scale, the historical fire regime, and presence of other environmental stressors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Stephenson and Bailey [ 17 ] found that cows on southern short grass prairie in central New Mexico, a site with terrain similar to DWR, had no HWI above 0.25 and 0.50 at 75 m and 500 m criteria, respectively. Clark et al [ 49 ] considered cattle behaving independently when they spent more than 75% of their time at distances greater than 75 m. Cattle in our study at the DWR appeared to distribute themselves independently based on this 75% of the time at greater than 75 m apart criterion. The low HWI of even the most associated dyads at 75 m suggests that cattle may have chosen grazing patch sites without strong influences from other GPS tracked cattle in the study.…”
Section: Discussionmentioning
confidence: 59%